Extreme waves and shock-exited processes in structures and space objects - Galiev, Shamilʹ Usmanovich (Boca Raton, FL : CRC Press, 2020)
The theory of waves is generalized on cases when waves change medium in which they appear and propagate. A reaction of structural elements and space objects to the dynamic actions of the different nature, durations, and intensities is studied. It considers the effects of transitions in the state and phase equations of media on the formation and propagation of extreme waves as a result of power, thermal, or laser pulsed action. The influence of cavitation and cool boiling of liquids, geometric and physical nonlinearity of walls on containers' strength, and the formation of extreme waves is studied. The theory can be also used to optimize impulse technology, in particular, in the optimization of explosive processing of sheet metal by explosion in a liquid. This book was written for researchers and engineers, as well asgraduate students in the fields of thermal fluids, aerospace, nuclear engineering, and nonlinear waves.
OCLC-licensed vendor bibliographic record.
Keywords: Waves; Shock waves; SCIENCE / Physics; TECHNOLOGY / Engineering / Mechanical